Theoretical Bases of Model of Intervention in Speech Therapy for Preschool Children with Phonological Insufficiency - Vilka, Ilze (Special Education, 2022)
At 5–6 years, most children pronounce all the sounds of their mother tongue correctly and have developed phonemic awareness, but not all children have reached an adequate level of speech and language development. In order to alleviate speech development and language acquisition disorders, it is necessary to carry out interventions based on sequential steps and activities. This article reveals the findings of various authors attempting to explain the action of such interventions. On the basis of the analysed literature, the author proposes a model of intervention in speech therapy for the reduction of phonological disorders.